Managing Performance Throughout Periods of Travel. Issue 4 (August 2017) - Williams, Biju; Clarke, Richard; Aspe, Rodrigo; Cole, Matthew; Hughes, Jonathan
Abstract : ABSTRACT: UNDERSTANDING THE IMPACT OF TRAVEL ON PHYSICAL PERFORMANCE IS AN INCREASING AREA OF INTEREST FOR THE STRENGTH AND CONDITIONING PRACTITIONER. PREVIOUS RESEARCH SURROUNDING THE EFFECT OF TRAVEL ON THE PHYSIOLOGY OF AN ATHLETE HAS FOCUSED ON SLEEP. OF CONCERN TO COACHES AND ATHLETES ARE STRATEGIES TO HELP ATTENUATE ANY DETRIMENTAL IMPACT OF TRAVEL ON SUBSEQUENT PERFORMANCE. THE AIM OF THIS ARTICLE IS TO PROVIDE INFORMATIVE PRACTICAL GUIDELINES FOR BEFORE, DURING, AND AFTER TRAVEL THAT CAN BE IMPLEMENTED BY COACHES AND ATHLETES. THE KEY COPING STRATEGIES ADDRESSED INCLUDE TIMED LIGHT EXPOSURE; MANAGING SLEEP DEPRIVATION AND NUTRITIONAL RECOMMENDATIONS.